Pineal yolk sac tumour with a solid pattern: a case report in a Chinese adult man with Down's syndrome. Issue 8 (27th July 2004) - Tan, H W; Ty, A; Goh, S G N; Wong, M C; Hong, A; Chuah, K L
Abstract : Intracranial germ cell tumours are rare. The incidence of primary intracranial yolk sac tumour is even more uncommon, with only two reported cases being associated with Down's syndrome in the English literature. This report details the findings of yolk sac tumour in the pineal region affecting a 22 year old Chinese man with Down's syndrome. Histology revealed yolk sac tumour with only a solid pattern, potentially mimicking the more common germinoma in the pineal region. No other germ cell components were identified. This is the third report of intracranial yolk sac tumour manifesting in a patient with trisomy 21. The pathology of this tumour and its differential diagnoses are discussed.